The Impact of a Booklet and Video on Reproductive Health Education on The Behavior of SMP Negeri 1 Tolitoli's Class IX Students - Evie, Sova; Hasni, Hasni; Suswinarto, Dwi Yogyo; Enggar, Enggar (Poltekita: Jurnal Ilmu Kesehatan, 2024)
Adolescent reproductive health issues stem from a lack of information, understanding, and awareness, leading to risky sexual behaviors. This study aimed to assess the effectiveness of reproductive health education using videos and booklets on the behavior of Class IX students at SMP Negeri 1 Tolitoli. A quasi-experimental design with pre- and post-test and control group was employed. The sample consisted of 138 students divided into two groups: video (n=69) and booklet (n=69). Behavior was measured before and 30 days after the intervention using a validated questionnaire. Data were analyzed using the Wilcoxon test. In the video group, mean knowledge increased from 00.00 to 24.50, mean attitude from 00.00 to 13.50, and mean action from 00.00 to 22.50. In the booklet group, mean knowledge increased from 15.00 to 16.11, mean attitude from 00.00 to 12.00, and mean action from 11.50 to 13.06. No significant difference in student behavior was found between the video and booklet groups (p<0.05). Education using videos and booklets was equally effective in changing student behavior. These findings highlight the importance of providing comprehensive reproductive health education to adolescents using engaging media to promote healthy behaviors and prevent risky sexual practices.